PELAKSANAAN PENDIDIKAN DAN LATIHAN (DIKLAT) DALAM UPAYA PENINGKATAN KUALITAS HIDUP PEREMPUAN OLEH BADAN KELUARGA BERENCANA DAN PEMBERDAYAAN PEREMPUAN (BKBPP) KABUPATEN KAMPAR - Dewiana "; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Still the gap between women's participation and the development of men, women's limitedaccess to the activities of the wider public, is part of the issues to be resolved. In addition,women's issues are complex and cut across the field, thus handling the problem can not becarried out by the Ministry of PP and PA alone. Therefore, it needs the support and cooperationamong all stakeholders, both the center and the regions, so that the condition can be handledproperly and thoroughly so, need to be established Agency for Family Planning and WomenEmpowerment (BKBPP) Kampar district. In order for the knowledge, abilities and skills of eachemployee can continue to evolve with the needs of the organization, the employee will need toobtain additional knowledge and skills in the provision of education and training. One of theprograms carried out by BKBPP Kampar district is Improving the Quality of Life of Women.Key Word : Education and Training, Quality of Life, Women